Hukuman Cambuk Di Aceh Dalam Prespektif Hadits Riwayat Muslim Dan Undang Undang 39 Tahun 1999 Tentang HAM - Khoirul Tamam; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2024)
Flogging punishment in Aceh has received great attention in the context of law and human rights. This study aims to determine the practice of flogging punishment in Aceh in terms of hadith and Law No.39 of 1999. Through a comparative analytical approach, it examines hadith related to flogging punishment in the context of Islam, especially Islamic history, and compares it with legal provisions. Contained in the Indonesian Human Rights Law No.39 of 1999. The study also examines the practice of corporal punishment in Aceh and its impact on society. The results reveal differences in interpretation of Islamic historical hadith and law enforcement in Aceh, as well as questions regarding adherence to human rights principles. The discussion aims to highlight the challenges and implications from a religious and legal perspective regarding corporal punishment in Aceh. The study provides valuable insights into understanding the complex power relations between religious traditions, positive law and human rights in specific local contexts